Immunoglobulins in Ducks and Role of Bursa of Fabricius in their Production - Krishnan Nair G (Department of Microbiology, College of Veterinary and Animal Sciences, 1990)
A study was undertaken to determine the immunoglobulin profile of ducks and to delineate the role of bursa in their production. Among the four different methods of bursectonomy employed in the study, Cy was found to produce the maximum reduction in body weight compared to other treatments. Marked reduction in bursal weight was also produced by Cy compared to T and ABS groups, while in SBx group the bursa was absent in toto. Surgical bursactomy resulted in significant reduction in spleen size of both surgically bursactomised uninoculated and inoculated ducklings. Histopathological studies revealed that the bursal development was highly suppressed on treatment with Cy. The ABS and testosterone treatments also elicited suppressive effect on bursa, but to a comparatively milder extent. It was evident that bursa had a role in lymphoproliferative reactions of spleen, as indicated by the maximum suppressive effect on spleen by SBx group. Ammonium sulphate at 33% level was found to be ideal for fractionation of duck serum globulins. Two main elution peaks were obtained on subjecting ammonium sulphate precipitated globulins to sephadex G – 200 chromatography. Concentrated and rerun ascending fractions of first major peak yielded purified IgM while those of the second major peak yielded purified IgG. Comparing the three age groups of antigen inoculation in ducklings bursectomised by different methods, total protein levels lower than the control were observed only in SBxSt (groups 1 and 11) and SBxSt (groups 1 and 111). Bacterial agglutination test revealed that in all four groups of bursectomised ducklings, antibody titres far below those of controls were produced. In SRBC agglutination test, lowered antibody titres than the control were observed in groups 1 to 111 of SBx, Cy and T – treated and groups 11 and 111 of ABS treated birds. Group 1 ABS administered ducklings had identical titres as that of control at days 7 – 21 post – inoculation. Bursectomized uninoculated ducklings revealed higher IgM levels than age – matched controls at many of the weeks under study. In bursectomised ducklings administered SRBC, IgM values higher than control level were obtained in the following cases : in groups 1 and 11 of SBxSR and TSR; groups 11 and 111 of CySR; and groups 1 to 111 of ABSR. S. typhimurium inoculated bursectomised ducklings revealed in the following treatments, higher IgM levels than control; in SBxSt groups 1 and 11; CySt groups 1 to 111; TSt group 1; and in ABSt groups 11 and 111. Quantitation of IgG levels in bursectomised ducklings revealed lower than control levels in SBx, Cy and T groups at 1 – 4 weeks of age, while the levels were higher or lower or identical with that of control from week 5. In ABS group the level was lower at 1 – 2 weeks. In bursectomised ducklings administered SRBC, higher IgG levels than control were obtained in groups 11 and 111 of SBxSR, CySR, TSR and ABSR. In group 1, treated ducklings revealed either lower or identical IgG levels compared to age matched controls. S. typhimurium inoculated bursectomised ducklings had higher IgG levels compared to CSt in all three groups of inoculation. Bile of ducks was found to contain only IgM, as evidenced by immunoelecrophoretic and quantitation studies. The IgM level in bile of bursectomised ducklings was found to be lower than that of the control. Yolk of duck eggs contained both IgM and IgG. Significantly higher lymphocyte count between the control and treated groups under study was detected at 4th (in SBx and T) and 8th weeks (in Cy). At 7th week, SBx group had significantly lower lymphocyte count, compared to control. At the fourth week of age, SBx and T groups had significantly lowered heterophil counts, compared to control. SBx group showed significantly higher count than the control at the 7th week, while at the 8th week, Cy – treated birds had markedly lower count, compared to the control. Eosinophil counts in bursectomised ducklings were higher than in control, while the basophil and monocyte counts in control and treated groups were more or less the same. The results obtained from the present study revealed that, 1. Among the different methods of Bx employed Cy produced maximum reduction in body weight, while SBx resulted in total elimination of bursa and significant reduction of spleen size. 2. Bursa had a role in lymphoproliferative reaction of spleen. Cy – produced maximum suppressive effect in bursa while in spleen SBx caused maximum suppression. 3. Ammonium sulphate (33%) was ideal for separation of duck serum globulins. 4. Sephadex G – 200 gel filtration was suitable for purification of IgM and IgG of ducks. 5. Bursa was concerned only with specific antibody production. 6. Elevated IgM and IgG levels were produced in bursectomised birds by extra – bursal B cells. 7. Bile of ducks contained IgM, the concentration of which was lower than the control in bursectomised birds. 8. Egg yolk of ducks contained both IgM and IgG.